Peran Lingkungan Keluarga Terhadap Kesejahteraan Emosional Anak Usia Dini: Studi Literatur - Filla Septi Wulandari; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Emotional well-being in early childhood is a fundamental aspect of child development that influences various areas of life, both in the short and long term. During early childhood, children experience rapid development, making their experiences especially within the family environment crucial in shaping their emotional condition. In recent years, issues related to children’s emotional well-being have increased, including aggressive behavior, difficulties in emotional regulation, and limited social interaction skills. These problems are closely related to the role of the family as the child’s first and primary environment. The quality of parent–child interaction, parenting styles, family communication, and family stability are key factors influencing children’s emotional development. Several studies indicate that lack of parental involvement, excessive use of digital devices, and family conflict can negatively affect children’s emotional well-being (Nurmalitasari, 2015; Wahyuni & Azizah, 2020; Rahman, 2021). This study aims to examine the role of the family environment in shaping early childhood emotional well-being through a literature review using 15 relevant sources. The findings show that attachment between children and parents, parenting styles, family communication, and family stability are the main factors influencing emotional well-being; therefore, active parental involvement in creating a warm, responsive, and stable family environment is essential to support optimal emotional development in early childhood